Investigating the Structure of Detachment Faulting and Its Role in Ore Formation: The Kallintiri Detachment System and the Associated Polymetallic Ore Deposit (Rhodope, NE Greece) - Konstantinos Soukis; Christos Kanellopoulos; Panagiotis Voudouris; Constantinos Mavrogonatos; Ilias Lazos; Sotiris Sboras; Alexandre Tarantola; Daniel Koehn; Robert Moritz (Geosciences)
The Kallintiri area (SW Byala Reka–Kechros Dome, Rhodope) hosts a polymetallic (critical, base, and precious metals) ore deposit, tectonically controlled by the late Eocene–Oligocene, top-to-SW Kallintiri Detachment System. The earliest structure associated with the Kallintiri Detachment is a ductile shear zone at the interface between the high-grade footwall gneisses of the Lower and Intermediate Rhodope Terranes. The detachment zone encompasses the uppermost part of the gneisses and the ultramylonitic Makri Unit marble. The marble is bound by a brittle–ductile shear zone at the base and a knife-sharp, low-angle normal fault at the roof, exhibiting considerable brecciation and ultracataclasite development. The hanging wall includes the Makri Unit phyllites and the overlying mid–late-Eocene–Oligocene supra-detachment sediments, which show syn-depositional slump structures and brittle deformation with low- and high-angle faulting and non-cohesive cataclasites. Extensive hydrothermal fluid circulation along the detachment zone and through NW tension gashes and high-angle faults led to pronounced silicification and ore deposition. Field observations and mineralogical and geochemical analyses revealed two primary types of ore mineralization spatially and temporally associated with different structures. Base and precious metals-rich ores are associated with the detachment, while Sb ore deposition is localized mostly within the NW-trending tension gashes and high-angle faults.